Neuropsychiatric Disorders in Chronic Kidney Disease - Simões e Silva, Ana Cristina; Miranda, Aline Silva; Rocha, Natalia Pessoa; Teixeira, Antônio Lúcio (Frontiers in Pharmacology, 2019)
Neuropsychiatric conditions including depression, anxiety disorders and cognitive impairment are common in patients with chronic kidney disease (CKD). These conditions often make worse the quality of life and also lead to longer hospitalizations and higher mortality. Over the past decades, some hypotheses have tried to explain the connection between CKD and neuropsychiatric disorders. The most common hypothesis is based on the occurrence of cerebrovascular disease and accumulated uremic toxins in adult patients with CKD. However, the lack of a direct association between known vascular risk factors like diabetes and hypertension with CKD-related cognitive deficits, the occurrence of neuropsychiatric comorbidities in pediatric patients with CKD preceding vascular damage, and the inconsistent findings on neuroprotective effects of antihypertensives suggest that other mechanisms, shared by renal and neuropsychiatric diseases, may also play a role. Therefore, the aim of this narrative review was to summarize clinical evidence and potential mechanisms that links CKD and brain disorders, specifically in regard to cognitive impairment, anxiety and depression.